Higher education through second chance educational oppotunities for underachievers : a case study of three higher learning institutions in the Maldives - Reesha, Aishath (Kulliyyah of Education, International Islamic University Malaysia, 2015)
This study explored the equity improving efforts by three higher education institutions in the Maldives to provide access to higher education for underachievers who had sat for the International Ordinary Level Examinations and failed in all the subjects. The tailor-made bridging programmes in these institutions begin with Certificate 3, and then move on from foundation to the degree. The step-by-step approach in the private higher education institutions provides the opportunity for underachievers to further progress in their academic pursuits. This study also examined the underachievers' success in further education from their own perspectives as well as from their teachers' perspectives. To address the research questions, multiple modes of data collection were used; namely, semi structured interviews, non-participant observations, and questionnaires. The convergent parallel design was used to triangulate the methods. This study also utilized thematic analysis to analyse qualitative data while descriptive statistics were used to analyse quantitative data. The participants for the study were selected using the purposive sampling method and comprise general underachievers and their teachers. The findings indicate that most of the underachievers in the three institutions firmly believed that they were capable of succeeding in higher education, with the teachers sharing a similar view. Better job and career opportunities and parental encouragement were cited as the main reasons for their motivation to pursue further studies. The majority of the students understood the benefits of higher education, and they were highly motivated to achieve their goal. Among the major challenges in the programme identified by the underachievers was the dearth in qualified teachers as well as the problems they faced while studying. Finally, the teachers were of the view that among the factors that hindered the students' ability to succeed were their lack of proficiency in English, their academic backgrounds in non-related subject areas, and their working, studying, and being young parents at the same time.